2021
DOI: 10.7150/jca.61602
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide, a subtype-selective histone deacetylase inhibitor, enhances Bortezomib effects in multiple myeloma therapy

Abstract: Drug resistance is the major cause for disease relapse and patient death in multiple myeloma (MM). It is an urgent need to develop new therapies to overcome drug resistance in MM. Chidamide (CHI), a novel oral HDAC inhibitor targeting HDAC1, 2, 3 and 10, has shown potential therapeutic effect in MM. In this study, we determined that CHI exhibited significant anti-tumor effect on MM cells both in vitro and in vivo, which was positively correlated with the expression of HDAC1. Meanwhile, CHI enhanced Bortezomib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Chidamide also exerted a synergistic effect with traditional antimyeloma agents, such as bortezomib. The combination of chidamide with bortezomib induced G0/G1 arrest and cell apoptosis, with increased ROS‐dependent DNA damage and impaired the cell cycle 47 . Additionally, chidamide was observed to cooperatively enhance the antimyeloma activity of bortezomib by repressing the autophagic degradation of ubiquitinated proteins 48 .…”
Section: Chidamide In Multiple Myelomamentioning
confidence: 99%
See 3 more Smart Citations
“…Chidamide also exerted a synergistic effect with traditional antimyeloma agents, such as bortezomib. The combination of chidamide with bortezomib induced G0/G1 arrest and cell apoptosis, with increased ROS‐dependent DNA damage and impaired the cell cycle 47 . Additionally, chidamide was observed to cooperatively enhance the antimyeloma activity of bortezomib by repressing the autophagic degradation of ubiquitinated proteins 48 .…”
Section: Chidamide In Multiple Myelomamentioning
confidence: 99%
“…The combination of chidamide with bortezomib induced G0/G1 arrest and cell apoptosis, with increased ROS-dependent DNA damage and impaired the cell cycle. 47 Additionally, chidamide was observed to cooperatively enhance the antimyeloma activity of bortezomib by repressing the autophagic degradation of ubiquitinated proteins. 48 Moreover, the bortezomib-resistant myeloma cell line ANBL6-BR showed higher HDAC1 expression, and this cell line was more sensitive to chidamide than the wild-type cell line.…”
Section: The Treatment Of Multiple Myeloma With Chidamide In Preclini...mentioning
confidence: 99%
See 2 more Smart Citations
“…Like other targeted therapies, drug resistance also occurs commonly in MM patients. He et al reported that tucidinostat could reverse bortezomib resistance through enhanced ROS production and DNA damage (He et al, 2021). ABT199 (Venetoclax) is a selective BCL-2 inhibitor approved as a component of combination therapy for AML.…”
Section: Hematological Malignanciesmentioning
confidence: 99%